Protective Effect of Shenfu Injection against Sepsis-induced Acute Lung Injury by Suppressing Inflammation and Apoptosis Through the Regulation of the Janus Kinase 2/Signal Transducer and Activator of Transcription 3 Pathway - Li-Juan Cao; Hai-Tang Xie; Zhong-Xia Chu; Yue Ma; Ming-Ming Wang; Shi Zhuang (World Journal of Traditional Chinese Medicine)
Objective: Sepsis-induced acute lung injury (ALI) is a clinically critical condition with a high mortality rate. Shenfu injection (SFI) is a Chinese herbal medicine extracted from red ginseng and Aconite, Radix Aconiti, with various pharmacological activities. This study aimed to investigate the potential mechanism of action of SFI in preventing sepsis-induced ALI. Materials and Methods: We established a mouse model of sepsis-induced ALI by cecal ligation and puncture (CLP). The mice were randomly divided into three groups (n = 8): Sham, CLP, and SFI (10 mL/kg). Bronchoalveolar lavage fluid (BALF) and lung tissue were collected for pathological analysis, enzyme-linked immunosorbent assay, immunohistochemistry (IHC), and protein detection. Results: Our results showed that SFI significantly ameliorated pathological damage caused by CLP-induced ALI. SFI treatment significantly decreased the lung wet-to-dry weight ratio. In addition, SFI treatment significantly reduced the protein levels and cell numbers in the BALF. SFI could significantly reduce the levels of tumor necrosis factor-α, interleukin-6 (IL-6), and IL-1β in plasma and BALF. SFI significantly reduced the protein expression of Bax and cleaved caspase-3 and increased the protein levels of Bcl-2. Western blotting and IHC results showed that SFI reduced the phosphorylation of Janus kinase 2 (JAK2) and signal transducer and activator of transcription 3 (STAT3). Conclusions: In a septic ALI mouse model, SFI inhibited apoptosis and inflammation through the JAK2/STAT3 pathway, providing a candidate drug for the treatment of septic ALI.